Photocatalytic Properties of Nanotubular-Shaped TiO2 Powders with Anatase Phase Obtained from Titanate Nanotube Powder through Various Thermal Treatments - Nam-Hee Lee; Hyo-Jin Oh; Sang-Chul Jung; Won-Jae Lee; Dong-Hyun Kim; Sun-Jae Kim (International Journal of Photoenergy)
Photocatalytic properties of nanotubular-shaped titanate powders, synthesized by hydrothermal treatment of TiO2, were studied after calcinations at various temperatures and times under O2, air, and H2 atmospheres. Their photocatalytic properties were measured with checking decomposition of 4-chlorophenol under UV-A irradiation, together with physical characterizations using SEM, TEM, XRD, BET, and Raman spectroscopy. With increasing calcination temperature and time, nanotubular-shaped titanate particles became short, rod-like, or irregular by oversintering, and their crystalline structure was changed into anatase phase. The photocatalytic ability in decomposition of 4-chlorophenol using the calcined powders showed the highest value due to obtainment of high specific area by maintaining nanotubular shape, together with transformation from titanate to anatase phase having perfect crystallinity in O2 or air atmosphere.